Hindsight Bias and Trust in Government - Herz, Holger; Kistler, Deborah; Zehnder, Christian; Zihlmann, Christian (The Review of Economics and Statistics, 2026)
We empirically assess whether hindsight bias affects citizens’ evaluation of their political actors. Using an incentivized elicitation technique, we demonstrate that people systematically misremember their past policy preferences regarding how to best fight the COVID-19 pandemic. At the peak of the first wave in the United States, the average respondent mistakenly believed that they supported significantly stricter restrictions at the onset of the first wave than they actually did. Exogenous variation in the extent of hindsight bias, induced through a randomized survey experiment, indicates that hindsight bias has a negative causal impact on the change in trust in government.